1957
DOI: 10.4141/cjss57-015
|View full text |Cite
|
Sign up to set email alerts
|

THE pH OF NON-CALCAREOUS NEAR-NEUTRAL SOILS

Abstract: Variations in [Formula: see text] have a pronounced effect on both pH and pH–1/2pCa of non-calcareous near-neutral soils. Consequently it is necessary to specify the [Formula: see text] at which the measurements are made regardless of whether pH or pH–1/2pCa is used to indicate the acidity of these soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1958
1958
1998
1998

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Uncertainties in the description of the IGM evolution (both its normalization, f g0 ∼ 0.1 ÷ 0.3 at the scale of rich clusters, and its evolution with time parametrized in terms of the parameters η ∼ 0 ÷ 0.9 and s ∼ 0 ÷ 1.5) are discussed to point out the role of different, possible gas-phase phenomena in cluster evolution. Here we take into account the minimal and maximal levels of IGM evolution that are still consistent -given the observational uncertainties -with the current data ([65] [25] [26] [28]).…”
Section: The Contribution Of Galaxy Clusters To the Dgrbmentioning
confidence: 99%
“…Uncertainties in the description of the IGM evolution (both its normalization, f g0 ∼ 0.1 ÷ 0.3 at the scale of rich clusters, and its evolution with time parametrized in terms of the parameters η ∼ 0 ÷ 0.9 and s ∼ 0 ÷ 1.5) are discussed to point out the role of different, possible gas-phase phenomena in cluster evolution. Here we take into account the minimal and maximal levels of IGM evolution that are still consistent -given the observational uncertainties -with the current data ([65] [25] [26] [28]).…”
Section: The Contribution Of Galaxy Clusters To the Dgrbmentioning
confidence: 99%
“…Gorham (1960) found that aeration of wet soils increased pH by reducing the tension of respired carbon dioxide. Nichol and Turner (1957) discussed the difficulties of interpreting the results of laboratory pH measurements of soils, pointing out that none of the methods gives results which can be directly related to field conditions. Humus pH is highest in midsummer and decreases as winter approaches, indicating that decreasing soil temperature decreases chemical and biological activity and causes decreases in soil pH.…”
Section: Resultsmentioning
confidence: 99%
“…However, the seasonal distribution of rainfall did not correspond to seasonal changes in humus reaction in this study. Nichol and Turner (1957) discussed the difficulties of interpreting the results of laboratory pH measurements of soils, pointing out that none of the methods gives results which can be directly related to field conditions. Gorham (1960) reported the range of pH values obtained from different humus types by three methods, i.e., insertion of glass electrodes into soil, into expressed solutions, and into aerated solutions.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous publication (4) was independent of the salt concentration. Table 3 shows that the pH increased as the soil/water ratio was decreased, but that pH-|pCa, pMg-pCa and pH-!p(Ca*MS) were independent of the ratio.…”
Section: Introductionmentioning
confidence: 98%